Good news: it’s not a sarcoma but a lobular capillary hemangioma - Banko, Nikodem; Chow, Chrissy; Stone, Jordan; Louis, Martine A.; Cantu, Roberto (International Surgery Journal, 2025)
Lobular capillary hemangioma (LCH), also known as pyogenic granuloma (PG), is a benign vascular tumor characterized by lobular proliferation of the capillaries that typically occurs in the head, neck, and oral mucosa. Occurrence in the extremities is uncommon and may mimic malignant soft tissue neoplasms. Although these masses can present at any age and in any race, with equal prevalence in men and women, they are more common in children, adolescents, young adults, and pregnant women. The diagnosis of LCH in atypical locations presents a challenge, particularly in young adults, due to the broad differential of both benign and malignant lesions with overlapping findings clinically and on imaging. Imaging with ultrasound or MRI may assist in characterizing the lesion, but it lacks specificity. Histopathological analysis remains the gold standard for diagnosis. Surgical excision serves diagnostic and therapeutic purposes, allowing for high resolution rates and low recurrence. We present the case of a 20-year-old male with a progressively enlarging soft tissue mass over the posterior right elbow, with magnetic resonance imaging raising initial concern for a soft tissue sarcoma. Surgical excision and histopathological analysis confirmed the diagnosis of LCH. This case underscores the importance of including benign vascular lesions such as LCH in the differential diagnosis of soft tissue masses, particularly in young adults.